The versatile roles and clinical implications of exosomal mRNAs and microRNAs in cancer. Issue 2 (June 2020) - Tang, Shuli; Yu, Siming; Cheng, Jianan; Zhang, Yanqiao; Huang, Xiaoyi
Extracellular vesicles (EVs), which include exosomes, microvesicles, and apoptotic bodies, are nanosized structures that are secreted by various cells and act as important mediators in intercellular communication. Recent studies have shown that exosomes carrying bioactive molecules are generated from multivesicular bodies and are present in various body fluids. mRNAs and microRNAs (miRNAs) are encapsulated in exosomes and have been found to be involved in multiple pathophysiological processes. Here, we provide a review of tumor-associated exosomal mRNAs and miRNAs and their roles in metastasis and drug resistance. In particular, we emphasize their clinical application potential as diagnostic and prognostic biomarkers of cancer and in cancer therapy.